Atrial Fibrillation: the Association with Physical Activity and the Effects of Cardiac Rehabilitation - M. G. Bubnova; D. M. Aronov (Столичная издательская компания, 2020)
The purpose of this review was to present modern studies that examine the relationship of physical activity and risk of atrial fibrillation (AF) development and the impact of cardiac rehabilitation programs in patients with all forms of AF. Data of 52 Russian and foreign scientific sources published in 1998- 2020 were presented. In our study, 48 patients with paroxysmal AF after radiofrequency ablation (RFA) were randomly assigned to a physical rehabilitation/standard therapy or control (standard therapy) group. Aerobic physical training was conducted for 6 months 3 times a week. AF is one of the most common cardiac arrhythmias. Despite modern advances, results of treatment of this disease are far from optimal. Many problems of patients with AF can be addressed through enrolment in multidisciplinary cardiac rehabilitation programs. But this question remains open. This is mainly due to the complexity of selection of physical rehabilitation program for patients with AF. It is known that physical activity can trigger an episode of AF. In the following review article, the approaches to functional capacity assessment of patient with AF are described, recommendations for prescribing safe exercise training to achieve a therapeutic effect are presented. Various aspects of the effects of physical rehabilitation are discussed, including its impact on cardiovascular risk factors, influence on atrial remodeling processes and associated biomarkers, prevention of AF progression and occurrence of cardiovascular complications. Results of our own research indicate effectiveness of physical training in patients with AF after RFA: increase in exercise duration by 18.6% (p<0.001) and load by 24.8% (p<0.01) during exercise test, increase in level of everyday physical activity by 23.8% (p=0.001); left atrium dimensions remain stable comparing with control group. That was combined with a decrease of post ablation atrial arrhythmias: after 6 months, they were registered in 4.5% of trained patients vs 17.4% of control group patients (p<0.01). Steady growth in the number of patients with AF and catheter ablation procedures around the world dictates the need for organization of multi-purpose medical rehabilitation.